2019
DOI: 10.21608/jhiph.2019.60843
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an Arabic version of the Short Form Modified Yale Food Addiction Scale

Abstract: Background: Food addiction (FA) is a growing problem worldwide, associated with physical and psychological dysfunction. The original Yale Food Addiction Scale (YFAS) was developed in 2009 for diagnosis of FA. Updated long and short forms of the Scale were developed in 2016 and 2017 respectively. An Arabic version of the updated short form suiting epidemiological purposes is lacking. Objective(s): The study aimed to adapt and test reliability of an Arabic version of the short form modified Yale Food Addiction S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This may be due to transcultural adjustment (i.e., the cross-cultural item adjustment affects the scale's original factor structure) and regional influences (e.g., the unique dietary habits in the area the study was carried out). Regarding the internal consistency, all previous studies have shown that the mYFAS 2.0 has a good α value (18,19,(21)(22)(23)(24)(25)47). Moreover, the concurrent validity verified through the correlations between food addiction and the selected measures have demonstrated good to excellent results in all previous studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This may be due to transcultural adjustment (i.e., the cross-cultural item adjustment affects the scale's original factor structure) and regional influences (e.g., the unique dietary habits in the area the study was carried out). Regarding the internal consistency, all previous studies have shown that the mYFAS 2.0 has a good α value (18,19,(21)(22)(23)(24)(25)47). Moreover, the concurrent validity verified through the correlations between food addiction and the selected measures have demonstrated good to excellent results in all previous studies.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the concurrent validity verified through the correlations between food addiction and the selected measures have demonstrated good to excellent results in all previous studies. BMI has been the most frequently used measure to examine the concurrent validity of the mYFAS 2.0 (19,21,22,47). Other measures such as impulsivity (21,23) and binge eating (19,22) have also been used in other studies as the validators and have found to be significantly associated with food addiction as assessed using the mYFAS 2.0.…”
Section: Discussionmentioning
confidence: 99%
“…The sixth part of the survey is related to the YFAS 2.0 SF, which was created in 2009 primarily to assess symptoms of addictive-like eating behavior and the difficulty in regulating food intake of such food types as candy, starches, salty snacks, fatty foods and other beverages such as sugary drinks [ 44 ]. The self-report, validated, modified and updated short forms of the Arabic version were used in the current study [ 45 ]. The Arabic version has 13 items, each of which is evaluated on an 8-point Likert scale from 0 to 7 on a range from “never” to “daily” over the last 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The mYFAS 2.0 has been successfully translated into various languages, such as Italian [ 6 ], French [ 7 ], Czech [ 8 ], Arabic [ 9 , 10 ], Brazilian Portuguese [ 11 ], Spanish [ 12 ], Turkish [ 13 ], Malay [ 14 ], traditional Chinese [ 15 , 16 ], and simplified Chinese [ 17 , 18 ]. Regarding Persian translations of the earlier YFAS [ 19 ] and YFAS 2.0 [ 20 ], A Persian version of the short form mPYFAS 2.0 that suits epidemiological purposes in Persian culture is lacking.…”
Section: Introductionmentioning
confidence: 99%